Selective pressure of PFOA on microbial community: Enrichment of denitrifiers harboring ARGs and the transfer of ferric-electrons. (15th April 2023) - Chen, Congli; Fang, Yuanping; Zhou, Dandan
Highlights: PFOA enhanced microbial denitrification by 178.6% in a porous media column. Denitrification gene abundances were related to ARGs harboring in denitrifiers. Nitrate reduction ferrous oxidizing bacteria (NRFOB) was the most sensitive group. Fe(II) oxidation drove denitrification by promoting electron donation for nitrate reduction. Abstract: Perfluorooctanoic acid (PFOA), a class of permanent organic pollutants, is frequently detected in surface and ground water, with the latter made up primarily of porous media (such as soils, sediments, and aquifers) that harbor microbial communities. Therefore, we investigated the effects of PFOA on water ecosystems and found that, under stimulation by 2.4 μM PFOA, denitrifiers were significantly enriched due to their hosting antibiotic resistant genes (ARGs), which were 1.45 times more abundant than the control. Furthermore, denitrifying metabolism was enhanced by Fe(II) electron donation. Specifically, 2.4 μM PFOA significantly enhanced the removal of total inorganic nitrogen by 178.6%. The microbial community became predominated by denitrifying bacteria (67.8% abundance). Notably, the nitrate-reduction ferrous-oxidizing (NRFO) bacteria Dechloromonas, Acidovorax, Bradyrhizorium, etc. were significantly enriched. The selective pressures of PFOA driving the enrichment of denitrifiers were twofold. First, the toxic PFOA induced denitrifying bacteria to produce ARGs, mainly including the efflux (occupying 55.4%) and antibiotic inactivation (occupying 41.2%) types, which improved microbial tolerance to PFOA. The risk of horizontal ARGs transmission was elevated as the overall number of horizontally transmissible ARGs increased by 47.1%. Second, Fe(II) electrons were transported via the porin-cytochrome c extracellular electrons transfer system (EET), promoting the expression of nitrate reductases, which in turn further enhanced denitrification. In summary, PFOA regulated the microbial community structure and influenced microbial TN removal functions and increased the contribution of ARGs by the denitrifier hosts, but the PFOA-induced production of ARGs may pose a serious ecological threat that needs to be comprehensively investigated. Graphical abstract: Image, graphical abstract